ANALISIS KESIAPAN PENERIMAAN PENGGUNA TERHADAP E-LEARNING MENGGUNAKAN MODEL TRAM - Sri Andayani; Rosalia Sonia Ono (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2020)
The development of technology in the world of education is characterized by the implementation of e-learning as a learning tool. E-learning as an application of educational technology deserves to be further utilized by the school / college because its existence is a new innovation in helping learners learn. The application of e-learning must of course be followed by the readiness of technology acceptance by all academic community. Readiness to accept the use of information technology can be defined as the user's willingness to use information technology to support the tasks that have been designed. To be able to see the readiness of technology acceptance today, you can use the two models developed, Technology Readiness (TR) and Technology Acceptance Model (TAM), which are used simultaneously, Technology Readiness and Acceptance Model (TRAM). TR and TAM models when integrated will produce an explanation of the intentions or desires of users in using technology.The results of this study are only discomfort variables that have asignificant effect on perceived usefulness while other variables do not significantly influence.